TABUNG HAJI MALAYSIA DALAM PERSPEKTIF EKONOMI - Nurhasanah, Nurhasanah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
The entity of Malay Muslims provide a heightened awareness to practice the teachings of Islam. Hajj as one of the fifth pillar of Islam is a priority agenda of empire since the early nineteenth century. The maintenance of Hajj initially became sultan  competence as a symbol of Islam in the Malay leadership. Thisis because the Malay customs affairs and the affairs of the religion of Islam to be the competence of the king, not the government or the British Empire